2019
DOI: 10.1186/s12916-019-1441-3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of linear growth faltering among children with moderate-to-severe diarrhea in the Global Enteric Multicenter Study

Abstract: BackgroundModerate-to-severe diarrhea (MSD) in the first 2 years of life can impair linear growth. We sought to determine risk factors for linear growth faltering and to build a clinical prediction tool to identify children most likely to experience growth faltering following an episode of MSD.MethodsUsing data from the Global Enteric Multicenter Study of children 0–23 months old presenting with MSD in Africa and Asia, we performed log-binomial regression to determine clinical and sociodemographic factors asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 53 publications
3
34
0
Order By: Relevance
“…Diarrhea is a leading cause of mortality accounting for more than 1.6 million deaths worldwide [1]. It causes nearly 5,25,000 deaths among children under 5 years of age and leads to malnutrition, stunted growth and anemia [2][3][4][5][6][7]. It is particularly prevalent in the low and middle-income countries owing to poor hygiene and sanitation.…”
Section: Introductionmentioning
confidence: 99%
“…Diarrhea is a leading cause of mortality accounting for more than 1.6 million deaths worldwide [1]. It causes nearly 5,25,000 deaths among children under 5 years of age and leads to malnutrition, stunted growth and anemia [2][3][4][5][6][7]. It is particularly prevalent in the low and middle-income countries owing to poor hygiene and sanitation.…”
Section: Introductionmentioning
confidence: 99%
“…The limited number of studies that aim to identify children most likely to growth falter after acute diarrhea have resulted in CPRs with varying discriminative and generalizability. Our full CPRs were better at identifying growth faltering than Brander et al (28) (AUC=0.67, 95% CI: 0.64, 0.69), which was not externally validated, and worse than Hanieh(35) et al (AUC: 0.85, 95% CI 0.80, 0.90), which only used data from a single country. The top predictors of growth faltering identified by random forests in our analysis were consistent with existing knowledge of the drivers of growth faltering – child demographics, child symptoms, and indicators of household wealth.…”
Section: Discussionmentioning
confidence: 57%
“…Children were excluded if follow-up observations occurred <49 or >91 days after enrollment, or if HAZ measurements were implausible (28), defined as: a) HAZ>6 or HAZ<-6; b) change in HAZ>3; c) >1.5cm loss of height from enrollment to follow-up; d) growth of >8cm or >4cm at 49-60 day follow-up for children ≤6 months and >6 months old, respectively; e) growth >10cm or >6cm at 61-91 day follow-up for children ≤6 months and >6 months old, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevention of diarrhea is critical for optimal growth and development among children. Specifically, it has been shown that the control of diarrhea during infancy and toddlerhood is critical to prevent stunted and faltered linear growth later in life (Moore et al 2001;Checkley et al 2003;Brander et al 2019). Infants and toddlers living in poor or remote communities are most at risk of diarrhea due to a lack of healthcare services and effective interventions.…”
Section: Introductionmentioning
confidence: 99%